The Analysis Of The Relationship Between Personality Types, Reflectivity, And Self-Efficacy Of EFL Teachers In Private Language Schools In Iran - Saniazar, Mehdi Mozaffar (2012)
The study was conducted to explore the relationship between Iranian English teachers‟ reflection levels, their self-efficacy, and their personality types. The purpose of this research is to find out if personality types of Iranian English teachers is related to their reflection level and/or self-efficacy levels, and hence to explore if teachers‟ self is a determining factor in their teaching practices. An additional aim of the study is to investigate if teachers‟ self-efficacy and their reflection levels are related, in order to find out if involvement in reflective practices makes teachers more effective. Establishment of a relationship between teacher personality on the one hand and reflective teaching and self-efficacy on the other, allows teacher educators to select and train teachers more effectively. Three instruments were employed to quantify the three constructs. Myers-Briggs Type Indicator (MBTI) was used to determine the participants‟ personality types. To measure their reflection levels, English Language Teaching Reflection Inventory (ELTRI) was used. The participants‟ self-efficacy was measured by Teachers‟ Sense of Efficacy Scale (TSES). First, MBTI was circulated among the randomly selected subjects to determine their personality types. Next, the subjects were randomly divided into experimental and control groups. In the pre-test phase, ELTRI (English Language Teacher Reflection Inventory) and TSES (Teachers‟ Sense of Efficacy Scale), which measure dependent variables of the study (teacher overall reflectivity and teacher overall self-efficacy), were distributed in both groups to measure their reflection and self-efficacy levels before the treatment. As the treatment, practical reflection (independent variable) was promoted in the experimental group. In the post-test phase, both control and experimental groups received ELTRI and TSES simultaneously in order to discover any possible changes. SPSS 16 was used for data analysis to answer the research questions. While the findings of this study confirmed a positive relationship between teacher reflection and self-efficacy, no significant relationship could be established between teachers‟ personality types and their levels of reflection. Teachers‟ self-efficacy and their personality types, however, were found related.